A Drosophila model for Meniere’s disease: Dystrobrevin is required for support cell function in hearing and proprioception - Requena, T.; Keder, A.; zur Lage, P.; Albert, J. T.; Jarman, A. P. (Frontiers in Cell and Developmental Biology, 2022)
Meniere’s disease (MD) is an inner ear disorder characterised by recurrent vertigo attacks associated with sensorineural hearing loss and tinnitus. Evidence from epidemiology and Whole Exome Sequencing (WES) suggests a genetic susceptibility involving multiple genes, including α-Dystrobrevin (DTNA). Here we investigate a Drosophila model. We show that mutation, or knockdown, of the DTNA orthologue in Drosophila, Dystrobrevin (Dyb), results in defective proprioception and impaired function of Johnston’s Organ (JO), the fly’s equivalent of the inner ear. Dyb and another component of the Dystrophin Glycoprotein Complex (DGC), Dystrophin (Dys) are expressed in support cells within JO. Their specific locations suggest that they form part of support cell contacts, thereby helping to maintain the integrity of the hemolymph-neuron diffusion barrier, which is equivalent to a blood-brain barrier. These results have important implications for the human condition, and notably, we note that DTNA is expressed in equivalent cells of the mammalian inner ear.